Peralihan Fungsi Benteng Pendem Cilacap Dari Masa Ke Masa - Adhiningtyas Putu Widharta; Emy Wuryani; Tri Widiarto (Cakrawala: Jurnal Pendidikan, 2018)
The purpose of this paper is to describe the establishment history of Benteng Pendem Cilacap and understand the function switch of it from the beginning until now. The central question of this study asks how is the function switch of Benteng Pendem from time to time. Therefore, historical method was applied in order to answer the question. Data for this research were collected using four stages: heuristic, source criticism, interpretation, and historical writing. The result showed that at first, Benteng Pendem was designed for military design of the Dutch-Indian government. However, at this current development, it was used for several function: 1) during the Japanese occupation, it was used as a military defense headquarters by Japanese soldier; 2) during the Indonesian independence, it was used as a place to practice for war and sea landing by the Indonesian national army (TNI) Banteng Loreng in Central Java; 3) at this time, Benteng Pendem Cilacap is one of Indonesia’s educational and historical excursion.